The First Death of My Father: Reflecting on Masculinity, Illness, and Work - Martínez, Alejandra (2016)
In this autoethnographic essay I reflect on the relationship between hegemonic masculinity and paid work. I draw on my own experience, witnessing my father retire at age 32 because of a mental illness that confined him to our home. I explore his personal despondency at failing to comply with traditional gender roles, as well as our collective family suffering.